The emerging role of long noncoding RNA RMRP in cancer development and targeted therapy - Hao, Qian; Zhou, Xiang (Cancer biology & medicine, 2022)
In a later study, we further reported that RMRP expression was upregulated in various human cancers, when compared with normal tissues, and upregulation of RMRP was significantly associated with unfavorable prognoses in breast cancer, head and neck carcinoma, lung adenocarcinoma, pancreatic ductal adenocarcinoma, stomach adenocarcinoma, and uterine corpus endometrial carcinoma4. [...]studies are needed to elucidate how PERK inhibits RMRP expression under ER stress. [...]posttranscriptional modifications contribute to RMRP expression by modulating its RNA turnover. Because miR-206 has been shown to inactivate multiple oncogenic signal transduction pathways in cancer, it is not surprising that RMRP is also able to regulate these pathways by counteracting miR-206. Figure 2 The RNA component of mitochondrial RNA-processing endoribonuclease (RMRP) promotes cancer cell growth and proliferation, inhibits apoptosis, drives the epithelial-mesenchymal transition and metastasis, and regulates energy metabolism by competitively interacting with numerous miRNA tumor suppressors.